Analysis of The Effect of Internal Control, The Quality of Human Resources and The Application of Accrual Basis on The Quality of Financial Statements in The Regional Government of Papua Province - Festus Reymon Kasse; Entar Sutisman; Sahrul Ponto (West Science Social and Humanities Studies, 2023)
This study aims to simultaneously analyze the effect of internal control, the quality of human resources, and the application of accrual bases on the quality of financial statements. This research uses a quantitative approach with a descriptive research paradigm, which emphasizes measuring research variables with numbers and conducting data analysis with statistical procedures. The purpose of this descriptive research is to test hypotheses or answer questions related to the current status of the subject under study, which can involve individuals, organizations, industries, or other perspectives. The results showed that internal control, the quality of human resources, and the application of accrual basis together have a significant positive effect on the quality of regional financial statements. Therefore, optimizing internal supervision, increasing the competence of human resources in accounting or finance, and implementing an accrual basis in each OPD in Papua Province can simultaneously improve the quality of local government financial statements.